Foreign Body Ingestion and Aspiration in the Pediatric Population: Analysis of 315 Cases. (23rd August 2013) - Truong, Anh Q.; Funamura, Jamie L.; Senders, Craig W.
Abstract : Objectives: 1) Determine the patient characteristics, presentation, location, and rates of associated injury in pediatric foreign body ingestion and aspiration. 2) Analyze the types of intervention and rates of postoperative complications. Methods: Retrospective analysis of all patients under the age of 18 who were evaluated for foreign body (FB) ingestion and aspiration at a tertiary care center between January 1, 2003, and December 31, 2012. Results: We identified 315 patients. 61% were male and 39% female, with an average age of 3.9 years (SD 3.9). 55.6% of FBs were found to in the esophagus, 22.2% in the airway, and 22% in the oropharynx or GI tract. The most common signs and symptoms at presentation were emesis (30.9%), choking/gagging (27.4%), coughing (24.0%), drooling (23.4%), and dysphagia (23.4%) with an esophageal FB and increased work of breathing (50.0%), cough (48.6%), choking/gagging (44.3%), wheezing (40.0%), and stridor (20.0%) with an airway FB. The most common FBs were coins (88.6%) and nuts/seeds (42.9%) in the esophagus and airway, respectively. Patients with a proximal esophageal FB were younger than patients with a distal esophageal FB (2.53 vs. 8.29 years). There was a 44% rate of superficial mucosal injury in the esophageal FB group. Rigid bronchoscopy and esophagoscopy were the most common methods of FB retrieval. There were no pneumothoraces and pneumomediastinum noted postoperatively. Conclusions: Aerodigestive FB ingestion and aspiration represent common problems in children. History, physical exam, and imaging are all key aspects of timely diagnosis, with rigid endoscopy as the mainstay of management.